What Drives the Reversal of the Gender Education Gap? Evidence from Germany - Regina T. Riphahn; Caroline Schwientek (Institute for the Study of Labor (IZA), 2015)
We study the mechanisms that are associated with the gender education gap and its reversal in Germany. We focus on three outcomes, graduation from upper secondary school, any tertiary education, and tertiary degree. Neither individual and family background nor labor market characteristics appear to be strongly associated with the gender education gap. There is some evidence that the gender gap in upper secondary education reflects the rising share of single parent households which impacts boys' attainment more than girls'. The gender education gap in tertiary education is correlated with the development of class sizes and social norms.
Keywords: I21; J16; 330; educational attainment; wage premium; gender gap